Harman Blennerhassett papers - Blennerhassett, Harman, 1765-1831.; Blennerhassett, Harman, 1801-1854.
Correspondence, journals, memoirs, articles (1806) for the Ohio Gazette, legal and financial papers, and other material relating, in part, to the trial of Aaron Burr for treason, the indictment of Blennerhassett for conspiracy with Burr, and the subsequent misfortunes experienced by the Blennerhassett family. Papers include a journal (1807 July 20-November 20) of Blennerhassett, his letters to his wife, Margaret Blennerhassett, and a manuscript volume attributed to Harman Blennerhassett, Jr. (1801-1854).
Correspondents include Henry William Paget, the Marquis of Anglesey, Dominic Blennerhassett, Joseph Lewis Blennerhassett, Henry Clay, Nathaniel Cox, Robert Emmet, John Langley, Joseph S. Lewis, Mordecai Lewis, Thomas Mullins, Vincent Nolte, Sir Robert Peel, Joseph Tyndall, Richard S. Wheatley, and Dudley Woodbridge.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Lawyer, planter, and scholar.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anglesey, Henry William Paget, -- Marquis of, -- 1768-1854 -- Correspondence; Blennerhasset, Dominic, -- 1799- -- Correspondence; Blennerhassett, Joseph Lewis -- Correspondence; Blennerhassett, Margaret, -- approximately 1778-1842 -- Correspondence; Burr, Aaron, -- 1756-1836 -- Trials, litigation, etc; Clay, Henry, -- 1777-1852 -- Correspondence; Cox, Nathaniel -- Correspondence; Emmet, Robert, -- 1792-1873 -- Correspondence; Langley, John -- Correspondence; Lewis, Joseph S. -- Correspondence; Lewis, Mordecai, -- 1748-1799 -- Correspondence; Mullins, Thomas -- Correspondence; Nolte, Vincent, -- 1779-1856 -- Correspondence; Peel, Robert, -- 1788-1850 -- Correspondence; Tyndall, Joseph -- Correspondence; Wheatley, Richard S. -- Correspondence; Woodbridge, D. -- Correspondence; Blennerhassett family; American newspapers -- Ohio; Trials (Treason); Lawyers; Plantation owners; Scholars